Pemberian Terapi Okupasi : Menggambar untuk Mengontrol Halusinasi Pendengaran Pada Pasien Skizofrenia - Litasari, Maulida; Fitria, Yeni (Pusat Penelitian dan Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2023)
Background: Hallucinations are often found in patients with mental disorders as one of the symptoms which hallucinations with depression are characterized by withdrawing and being alone. Giving occupational therapy can improve mental health, social inclusion and also respect yourself by keeping yourself busy doing useful activities. This descriptive case study aims to provide an overview of how occupational drawing therapy is used to control auditory hallucinations in schizophrenic patients. Method: This qualitative research uses descriptive case studies with a nursing process approach. One participant, namely a schizophrenic patient with nursing problems with sensory perception disorders, and auditory hallucinations. Results: After implementation, the patient showed a decrease in symptoms. In session 1, the patient draws hallucinatory voices, in session 2, the patient draws his feelings, in session 3, the patient draws his wishes. Initially, the patient was seen chatting to himself, smiling to himself, lacking eye contact, and being more aloof. After being given therapy, the patient seemed to stop talking and laughing to himself. Conclusion: Occupational drawing therapy can focus the patient's mind and solve the hallucinations that come.